Optimization of mechanical and antioxidant properties of edible film based on grape juice and cross-linked maize starch and evaluation of its effects on the storage quality of fresh-cut pineapple - Yildirim-Yalcin, Meral; Sadikoglu, Hasan; Seker, Mahmut (SPRINGER, 2021)
Edible film with maximum tensile strength (TS), elongation at break (EAB), and antioxidant capacity were obtained with 29.42:70.58 (v/v) of grape juice (GJ): water volume ratio, 5% (w/v) of cross-linked maize starch (CLMS), and 0.5% (w/v) of glycerol by using Box-Behnken design. The optimum formulated film was tested in the preservation of fresh-cut pineapple slices. Oxygen concentration at headspace did not change significantly for coated pineapple but decreased from 20.60% to 18.43% for uncoated pineapple during storage. Insignificant reduction for the antioxidant capacity of coated samples between the 4th and 12th days showed that grape polyphenols of coating prevented the passage of oxygen through the coating. The coating saved the color and sensory properties of pineapple samples. Also, it decreased both elevations of total mesophilic aerobic counts and yeast & mold counts significantly due to the reduction of respiration with restricted oxygen and the antioxidant property. Results showed that coating pineapple with film including grape juice and cross-linked starch can be used to extend the shelf life of fresh-cut pineapple.
Keywords: Edible coating; Oxidation; Grape juice; Cross-linked starch; Shelf life; Pineapple; TOTAL PHENOLIC CONTENTS; SHELF-LIFE; COATINGS; CHITOSAN; BARRIER; Food Science & Technology